Cancer and coping with it - salemi S (Iran University of Medical Sciences, 1994)
In this paper the process of coping with cancer has been discussed. There is no doubt that cancer is a burden experience. There are two plans which represent coping demands and methods of coping with cancer. Coping demands have been experienced and reported by cancer patients. The most important method of coping is to find an opportunity for emotional coping. Study results represent that a large number of cancer patients feel shock, unreal feelings, fear, sorrow and anger. Nurses can help patients how to live with these feelings. It is very important for the patient to be supported from anxious in initiation of disease. The patient should be helped to be independent and active. We should know that cancer patients can not be able to cope with cancer without help of nurses or others. Patients who had jobbed reported that they have been able to come over with their problems. To be able to help these patients, nurses should be familiar with coping mechanisms which patients use. Nurses can inform patients and give them opportunity to present their feelings.